Institutional ownership, growth opportunity and corporate risk taking: Evidence from Malaysia public listed firms - Hanis Hazwani, Ahmad (2016)
This study investigates the effects of institutional ownership and growth opportunity on corporate risk taking. The relationships are examines using a sample of 522 nonfinancial firms from Bursa Malaysia with a 15 years timespan covering from the year 2000 until 2014. There is limited attention in the literature in regards to corporate risk taking. Volatility of corporate earnings is used to proxy for corporate risk taking. The main independent variables are institutional ownership and growth opportunity, while firm age, firm size, tangibility, leverage and profitability are included control variables. This study reports robust evidence that institutional ownership is negatively associated to corporate risk taking. This findings indicates that institutional shareholders that act as a monitoring mechanism have the capabilities to monitor and control the managerial activities to safeguard and to mitigate the excessive risk taking behaviour. However, the evidence on growth opportunity is not consistently significant, suggesting the need to further explore this relationship. Moreover, this study finds that firm age, firm size, leverage, tangibility and profitability are associated to corporate risk taking